Hadith #382 - Sahih al-Bukhari - Abu 'Alqama أبو علقمة (Sahih al-Bukhari)
Sa`id bin Yazid Al-Azdi: I asked Anas bin Malik whether the Prophet (ﷺ) had ever, prayed with his shoes on. He replied “Yes.”
Grade: Sahih